The Role of miRNAs in the Resistance of Anthracyclines in Breast Cancer: A Systematic Review - Si, Zihan; Zhong, Yan; Lao, Sixian; Wu, Yufeng; Zhong, Guoping; Zeng, Weiwei (Frontiers in Oncology, 2022)
Breast cancer has been reported as the most common cancer in women globally, with 2.26 million new cases in 2020. While anthracyclines are the first-line drug for breast cancer, they cause a variety of adverse reactions and drug resistance, especially for triple-negative breast cancer, which can lead to poor prognosis, high relapse, and mortality rate. MicroRNAs (miRNAs) have been shown to be important in the initiation, development and metastasis of malignancies and their abnormal transcription levels may influence the efficacy of anthracyclines by participating in the pathologic mechanisms of breast cancer. Therefore, it is essential to understand the exact role of miRNAs in the treatment of breast cancer with anthracyclines. In this review, we outline the mechanisms and signaling pathways involved in miRNAs in the treatment of breast cancer using anthracyclines. The role of miRNA in the diagnosis, prognosis and treatment of breast cancer patients is discussed, along with the involvement of miRNAs in chemotherapy for breast cancer.